USE OF APPLICATION OF LETTER AGENDA MANAGEMENT INFORMATION SYSTEM (SIMAS) AT CENTER FOR UPPER LIVESTOCK BREEDING AND FORGIVE LIVESTOCK FEED BATURRADEN BANYUMAS REGENCY - Sartono Sartono; Teguh Teguh (Department of Public Administration, University Wijaykusuma Purwokerto, 2022)
The purpose of this study was to describe the use of Management Information System Applications in the Management of Incoming and Outgoing Letters at the Baturraden Center for Superior Cattle Breeding and Forage. The data analysis technique used in this study is a descriptive qualitative approach with an interactive model using the